Evaluasi Kelayakan Usaha Penggemukan Sapi Potong Gaduhan di Desa Grantung Kecamatan Bayan Kabupaten Purworejo (The Feasibility Evaluation of Beef Cattle Fattening by Sharing System in Grantung Vilage, Bayan Subdistrict of Purworejo Regency) - Zulfanita (Zulfanita); Made Arya Wiguna; Sudi Nurtini (Buletin Peternakan, 2009)
The aim of the study was to find out the feasibility of beef cattle fattening by sharing system in Grantung, Bayan, Purworejo. The location of the research was in the village of Grantung, the subdistrict of Bayan, Purworejo Regency. The study was conducted from June until December 2006. The resopondents were the receivers of sharing system beef cattle from Agricultural and Husbandary Agency of Purworejo as many as 30 people which were taken by purposive sampling. Measurement of Benefit Cost ratio (BCR), Net Present Value (NPV) and Internal Rate of Return (IRR) values were done to analyse the feasibility. The result showed that values being obtained for BCR was 1.05; NVP was Rp. 1,798,664.07; and IRR was 31%. Therefore, it could be concluded that the beef cattle fattening by sharing system carried out in Grantung, Bayan, Purworejo was feasible to be implemented.(Key words: Beef cattle fattening, Sharing system, Project feasibility)